2015
DOI: 10.1039/c4cp04248d
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of “new hot spots” from determining the nonlinear optical behavior of materials: mechanistic studies of the vanadium borate crystal, Na3VO2B6O11

Abstract: A novel mechanism for the nonlinear optical (NLO) effects of vanadium borate crystals, Na3VO2B6O11 (NVB), with distorted VO4 groups was investigated. A comprehensive analysis of the structure-property relationship was performed by combining the experimental measurements, the electronic structures calculations, the SHG-weighted electron density and the real-space atom-contribution analysis to yield the linear and nonlinear optical properties. The contribution of a (VO4)(3-) anionic group to the second harmonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 80 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…An exhaustive enumeration of all the possible multi‐ternary cation combinations is impossible, and hence intuitive guidance is imperative for future success. For nonlinear optical (NLO) borate materials, it has been consistently shown that the presence of metal‐centered groups (e.g., Pb−O and V−O groups), which induce the hybridization states with O‐2p, is beneficial for the states close to the band gap dominating the optical properties of a crystal, whereas delocalized conduction bands of n s 1 cations (Na + , Rb + , Cs + ) are desirable for large band gaps and have success in producing NLO‐active materials with shorter optical absorption at around 220 nm. Fortunately, the direct combination of n s 1 (Na + , Rb + , Cs + ) and n s 2 (Ba 2+ ) cations generally maintains the large band gaps of the borates.…”
Section: Resultsmentioning
confidence: 99%
“…An exhaustive enumeration of all the possible multi‐ternary cation combinations is impossible, and hence intuitive guidance is imperative for future success. For nonlinear optical (NLO) borate materials, it has been consistently shown that the presence of metal‐centered groups (e.g., Pb−O and V−O groups), which induce the hybridization states with O‐2p, is beneficial for the states close to the band gap dominating the optical properties of a crystal, whereas delocalized conduction bands of n s 1 cations (Na + , Rb + , Cs + ) are desirable for large band gaps and have success in producing NLO‐active materials with shorter optical absorption at around 220 nm. Fortunately, the direct combination of n s 1 (Na + , Rb + , Cs + ) and n s 2 (Ba 2+ ) cations generally maintains the large band gaps of the borates.…”
Section: Resultsmentioning
confidence: 99%
“…To further confirm that the asymmetric NaQ 4 units could be used as NLO‐active units, we carried out statistical analyses on the origins of the SHG effect in the Na‐containing chalcogen compounds in the Inorganic Crystal Structure Database (ICSD), as shown in Tables S6–7 and Figures S9–10 in the Supporting Information. Based on the analyses of Mulliken overlap population in the NaS 4 units (Figure S10 in the Supporting Information), we can see that the shorter bond length can produce stronger overlap of the charge density in ionic Na−S bonding [60, 61] . Meanwhile, the NaS 4 units show a significant contribution to the SHG response if the value of Na−S Mulliken overlap population in the NaS 4 units exceeds about 0.2.…”
Section: Resultsmentioning
confidence: 93%
“…Using the length-gauge formalism at a zero frequency limit, the SHG coefficients can be estimated, which can be described as a later developed transform by Zhang et al: Here, the total SHG coefficient χ αβγ (2) is divided into the contribution from two different processes which are virtual-electron (VE) and virtual-hole (VH) . The theoretical methods have been applied with success to analyze the SHG coefficients of NLO crystal materials in previous study. , …”
Section: Methodsmentioning
confidence: 99%